2003
DOI: 10.1289/ehp.6466
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated diphenyl ethers (PBDEs) in U.S. mothers' milk.

Abstract: No previous reports exist on polybrominated diphenyl ether (PBDE) congeners in human milk from individual U.S. mothers. This article on PBDEs is an extension of our previous studies on concentrations of dioxins, dibenzofurans, polychlorinated biphenyls, and other chlorinated organic compounds in human milk in a number of countries. PBDE commercial products are used as flame retardants in flexible polyurethane foam (penta-BDE), in acrylonitrile-butadiene-styrene resins (octa-BDE), and in high-impact polystyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
250
8
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(280 citation statements)
references
References 48 publications
16
250
8
6
Order By: Relevance
“…The concentrations found in our study were slightly lower than those in the United Kingdom (Kalantzi et al, 2004) and Australia (Toms et al, 2007), and were one order of magnitude lower than those reported in the United States (Schecter et al, 2003). However, BDE-209 in this study exhibited relatively higher concentrations than those observed in the United States (Schecter et al, 2003), Norway (Thomsen et al, 2010), and Japan . These findings might be explained by the amount and different types of PBDEs technical formulations used in different regions.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The concentrations found in our study were slightly lower than those in the United Kingdom (Kalantzi et al, 2004) and Australia (Toms et al, 2007), and were one order of magnitude lower than those reported in the United States (Schecter et al, 2003). However, BDE-209 in this study exhibited relatively higher concentrations than those observed in the United States (Schecter et al, 2003), Norway (Thomsen et al, 2010), and Japan . These findings might be explained by the amount and different types of PBDEs technical formulations used in different regions.…”
Section: Discussioncontrasting
confidence: 83%
“…Compared with the general populations in other countries (Table 2), the PBDEs concentrations in milk in this study fell within the same range as those reported in Asian countries such as Japan (Eslami et al, 2006;Inoue et al, 2006), Indonesia (Sudaryanto et al, 2008a), Korea (Haraguchi et al, 2009), and the Philippines (Malarvannan et al, 2009), and from European countries such as Norway (Thomsen et al, 2010), France (Antignac et al, 2009), Spain (Gömara et al, 2007) and Belgium (Colles et al, 2008). The concentrations found in our study were slightly lower than those in the United Kingdom (Kalantzi et al, 2004) and Australia (Toms et al, 2007), and were one order of magnitude lower than those reported in the United States (Schecter et al, 2003). However, BDE-209 in this study exhibited relatively higher concentrations than those observed in the United States (Schecter et al, 2003), Norway (Thomsen et al, 2010), and Japan .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the PBDE burden of these patients was much lower than among occupational workers (with a mean PBDEs of 600 ng/g lipid) from Guiyu, as reported by Bi et al (2007). Nevertheless, the level of PBDE burden in the patient population was higher than those in the general European and Asian populations, which were generally below 5 ng/g lipid (Furst, 2006;Inoue et al, 2006;Lorber, 2008;Schecter et al, 1996Schecter et al, , 2003). Generally, North Americans tend to have higher body burdens of PBDEs than Europeans and Asians (Hites, 2004;Sjödin et al, 2003;Wang et al, 2007).…”
Section: Pbde Concentration In Human Semen Compared With In Human Bloodmentioning
confidence: 58%
“…Levels of PBDEs found in human tissues in North America are particularly alarming, as they are one to two orders of magnitude higher than those reported in Europe and Japan (Petreas et al 2003;Schecter et al 2003;Inoue et al 2006). Sources of PBDE exposure can be found in the occupational setting, in the diet, and in the indoor environment.…”
Section: Human Exposure and Body Burdenmentioning
confidence: 97%